The summary and reading skill. (Journal of Parents and Teachers, 2013)
This article makes a reflection about the reading and summarizing teaching process in Spain along the different educational levels. It starts from PISA results to argue that it is necessary a reflection and change in this tasks in which the family must be also included. The author parallel makes an analysis of Finland situation, the country with the best results in these aspects in such report. The author starts from the idea that the fundamental characteristic of competent reading is the comprehension that implies the interaction between the information and the previous knowledge that the reader already had. The summary results a key tool to confirm that the process has been made.
Keywords: Reading comprehension; abstract; teaching; prior knowledge; didactic; education.